Analysis of Merchandise Inventory Accounting Information System at PT Konimex Bengkulu City - Likhatus Sakdah; Yun Fitriano; Abdul Rahman (Penerbit Jurnal Indonesia, 2022)
The company PT Konimex Bengkulu City is one of the companies engaged in the distribution of food, vitamins, medicines and medical devices, especially in the Bengkulu City area. In the face of competitive competition, the company must improve the company's performance, through increasing the marketing of merchandise inventory to strengthen and improve the company's competitiveness. The purpose of this study was to determine the accounting information system for merchandise inventory at PT Konimex Bengkulu City based on the latest stock of goods in the merchandise warehouse. This type of research uses a qualitative approach, which is presented in a descriptive form that is not in the form of numbers and supports quantitative data as information, data collection methods are observation, interviews and documentation. In accounting there are several methods, namely FIFO, LIFO and Average. The results of this study found that the accounting information system for merchandise inventory at PT Konimex Bengkulu City uses the FIFO method where this method is used by manufacturing-based companies. PT Konimex Kota Bengkulu uses the FIFO method analysis because this company sells products that have an expiration date such as vitamins, food, and medicines.